Mesenchymal cells condensation-inducible mesh scaffolds for cartilage tissue engineering. (April 2016) - Kim, In Gul; Ko, Jaehoon; Lee, Hye Rim; Do, Sun Hee; Park, Kwideok
Abstract: Mesenchymal cells condensation is crucial in chondrogenic development. However current tissue-engineered scaffolds for chondrogenesis pay little attention to this phenomenon. In this study, we fabricate poly(l -lactide-co-glycolide) (PLGA)/poly(l -lactide) (PLLA) microfiber scaffolds and coat them with human fibroblast-derived matrix (hFDM) that is a decellularized extracellular matrix (ECM) obtained from in vitro cultured human lung fibroblasts (WI-38). Those scaffolds were then conjugated with heparin via EDC chemistry and subsequently immobilized with transforming growth factor (TGF)-β1. The amount of TGF-β1 was quantitatively measured and the release profile showed a continuous release of TGF-β1 for 4 weeks. Human umbilical cord blood-derived mesenchymal stem cells (UCB-MSCs) were seeded in four different scaffolds; control, fibronectin (FN)-coated, hFDM-coated, hFDM/TGF-β1 and subjected to chondrogenic differentiation in vitro for up to 28 days. Both hFDM and hFDM/TGF-β1 groups exhibited significantly more synthesis of glycosaminoglycan (GAG) and much better upregulation of chondrogenic markers expression. Interestingly, MSCs condensation that led to cell aggregates was clearly observed with time in the two hFDM-coated groups and the quantitative difference was obvious compared to the control and FN group. A mechanistic study in gene and protein level indicated that focal adhesion kinase (FAK) was involved at the early stage of cell adhesion and cell–cell contact-related markers, N-cadherin and neural cell adhesion molecule (NCAM), were highly up-regulated at later time point. In addition histological analysis proved that hFDM/TGF-β1 group was the most effective in forming neocartilage tissue in a rabbit articular cartilage defect model. Taken together, this study demonstrates not only the positive effect of hFDM on chondrogenesis of MSCs and cartilage repair but also provides an important insight toward the significance of in vitro mesenchymal condensation on chondrogenic development of MSCs.